PKM Pemberdayaan Masyarakat dalam Pengembangan Produk Olahan Pisang Sale Sidodadi Ramunia - Nurmala Berutu; Zulkarnain Siregar; Dwi Budiwiwaramulja; Hodriani Hodriani (Universitas Medan Area, 2020)
This community service program generally aims to increase the income of housewives in processing banana sale products in Sidodadi Village, Beringin District, Deli Serdang Regency. This service has specific targets and outcomes. Specific targets and outputs that will be produced include: One article published through ISSN online journals, Publications in mass print / online / university repository, Increasing competitiveness (increasing quality, quantity, and value added of goods, services, trademarks ), Increasing the application of science and technology in society, Improving community values (arts, culture, social, peace, education, health). The method of approach in the implementation of community service activities, through the method of exposure and discussion, training, assistance, simulation, observation, interviews, field notes, and cooperation with the main objective to improve the economy of the village of Sidodadi Romania through processing banana sale.